2008
DOI: 10.1111/j.1538-7836.2008.02987.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor‐bearing microparticles derived from tumor cells: impact on coagulation activation

Abstract: Summary. Background: Tissue factor (TF)-bearing microparticles (MP) from different origins are thought to be involved in the pathogenesis of cancer-associated thrombosis. However, the role of circulating tumor cell-derived TF is not well understood. Methods: TF antigen and activity were measured in MP generated in vitro from human TF-expressing cancer cells by ELISA and clotting or thrombin generation assays, respectively. TF antigen and activity were also measured in vivo in cell-free plasmas from mice previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
138
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(149 citation statements)
references
References 22 publications
9
138
0
2
Order By: Relevance
“…It is supposed that the direct toxic effect of anticancer treatment on cancer cells may lead to an increase in CTC fragments or microparticles with procoagulant activity (Dvorak et al, 1983). Circulating tumour cells could be involved in the activation of coagulation through the expression and release of tissue factors (TFs) (Davila et al, 2008). It was shown that TFs are overexpressed in cells with cancer stem cell phenotype (Milsom et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is supposed that the direct toxic effect of anticancer treatment on cancer cells may lead to an increase in CTC fragments or microparticles with procoagulant activity (Dvorak et al, 1983). Circulating tumour cells could be involved in the activation of coagulation through the expression and release of tissue factors (TFs) (Davila et al, 2008). It was shown that TFs are overexpressed in cells with cancer stem cell phenotype (Milsom et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…22 Further, plasma from these tumor-bearing mice was found to enhance thrombin generation in vitro in a human TF-dependent manner. 22 Another study found that human (SOJ-4) and mouse (PANC02) pancreatic cell lines expressed TF, and the investigators observed an accumulation of tumor-derived MPs at the site of thrombosis and increased thrombosis in a microvascular model. 18 The objective of the present study was to determine the role of tumor-derived TF in the activation of coagulation and thrombosis in a xenograft mouse model of human pancreatic tumors.…”
Section: Introductionmentioning
confidence: 99%
“…21 In nude mice bearing orthotopic human pancreatic tumors (L3.6pl) plasma levels of human TF protein were correlated with the levels of thrombin-antithrombin (TAT) complex, a marker of the activation of coagulation. 22 Further, plasma from these tumor-bearing mice was found to enhance thrombin generation in vitro in a human TF-dependent manner. 22 Another study found that human (SOJ-4) and mouse (PANC02) pancreatic cell lines expressed TF, and the investigators observed an accumulation of tumor-derived MPs at the site of thrombosis and increased thrombosis in a microvascular model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…26 Clearance of tumorderived human TF + MPs was examined in control and splenectomized mice. 27 In control mice, peak levels of TF + MPs were observed at 30 minutes, and none were detected at 120 minutes; whereas in the splenectomized mice, significant levels of TF + MPs were observed at 120 minutes. These results support the conclusion that the spleen is the major site for the clearance of PS + MPs with or without TF.…”
Section: Discussionmentioning
confidence: 90%